Graphene dispersion, graphene resin powder and battery
By adjusting the viscosity and viscosity ratio of the graphene dispersion liquid, the aggregation problem of graphene in the dispersion medium is solved, and a resin film with high conductivity is formed, which is used for the negative electrode material of the battery, and the discharge capacity retention rate of the battery is improved.
Patent Information
- Application Number
- CN202180051560.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-28
- Filing Date
- 2021-08-27
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-08-27
AI Technical Summary
Graphene is difficult to disperse well in the dispersion medium, and is prone to aggregation due to van der Waals forces. The dispersion is reduced when dried. The polymer content leads to an increase in surface resistance and reduced conductivity. Polyvinylpyrrolidone has the risk of film making.
By dispersing graphene and polymers in a solvent, adjusting the viscosity and viscosity ratio, the graphene dispersion has structural viscosity, reducing aggregation, improving coating property and film formation, and dispersing it again to form dispersion using dried graphene resin powder to form dispersion A film with good properties is used in the negative electrode material of secondary battery.
实现了石墨烯分散性良好、导电性高的树脂膜形成,提高了电池的高倍率放电容量保持率。
Smart Images

Figure BDA0004088009860000151 
Figure BDA0004088009860000161
Abstract
Description
Technical Field
[0001] The invention relates to a graphene dispersion liquid, a graphene resin powder and a battery, and in particular to a graphene dispersion liquid, a graphene resin powder obtained by drying the graphene dispersion liquid, and a battery obtained by using the graphene resin powder. Background Art
[0002] Graphene is a substance containing two-dimensional crystals composed of carbon atoms and is a very popular material. Graphene has excellent electrical, thermal, optical and mechanical properties. Graphene is expected to be widely used in fields such as graphene-based composite materials, nanoelectronic devices, flexible / transparent electronic devices, nanocomposites, supercapacitors, batteries, hydrogen storage, nanomedicine, and bioengineering materials. In particular, films dispersed with graphene are expected to be used as electromagnetic wave shielding materials, electromagnetic wave absorbing materials, electrode materials for fuel cells, heat dissipation materials, etc.
[0003] In order to form a film dispersed with graphene, it is necessary to disperse the graphene in a dispersion medium. Here, as a material obtained by dispersing graphene in a dispersion medium, a known thermoplastic resin and a carbon material with a graphene structure are dissolved or dispersed in a halogenated aromatic solvent to form a dispersion liquid (refer to patent document 1). In addition, as a material obtained by dispersing graphene in a dispersion medium, a known dispersion liquid obtained by stably dispersing graphene in a solvent by polymethylpyrrolidone (refer to patent document 2).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-224810;
[0007] Patent document 2: Japanese Patent Application Publication No. 2014-009104. Summary of the invention
[0008] The present invention relates to the following contents.
[0009] [1] A graphene dispersion, wherein graphene and a polymer are dispersed or dissolved in a solvent, wherein the polymer has a weight average molecular weight of 10,000 to 800,000, and the viscosity of the graphene dispersion measured using a B-type viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm is 500 to 10,000 (mPa·s), and the value obtained by dividing the viscosity of the graphene dispersion measured using a B-type viscometer at a measurement temperature of 25° C. and a rotation speed of 5 rpm by the viscosity of the graphene dispersion measured using a B-type viscometer at a measurement temperature of 25° C. and a rotation speed of 50 rpm is 1.2 to 5.0.
[0010] [2] A graphene resin powder obtained by drying the graphene dispersion described in [1] above.
[0011] [3] A battery using the graphene resin powder described in [2] above. DETAILED DESCRIPTION
[0012] Since graphene has a tendency to agglomerate due to van der Waals forces, it is difficult to make graphene well dispersed in a dispersion medium. In addition, for graphene dispersion liquid, when the solvent is dried to form a film, graphene has the risk of reagglomeration and reducing dispersibility. In addition, when the dispersion liquid contains a large amount of polymers, there is a polymer component on the surface when it becomes a film, and there is a risk that the surface resistance rises and the conductivity decreases. In addition, when the dispersion liquid contains polyvinyl pyrrolidone, there is a risk that film cannot be made.
[0013] The inventor dispersed graphene and a polymer of a specified weight average molecular weight in a solvent, and adjusted the value measured using a B-type viscometer at a measurement temperature of 25°C and a rotation speed of 50rpm (hereinafter, the viscosity measurement is the value measured using a B-type viscometer) to a specified range. In addition, the inventor adjusted the value obtained by dividing the viscosity measured at a measurement temperature of 25°C and a rotation speed of 5rpm by the viscosity measured at a measurement temperature of 25°C and a rotation speed of 50rpm to a specified range. As a result, it was found that a graphene dispersion having good dispersibility and capable of forming a graphene resin film with high conductivity can be obtained.
[0014] Furthermore, when the obtained graphene dispersion is dried to obtain a graphene resin powder, a graphene dispersion having good dispersibility is obtained when it is dissolved again in a solvent. The present inventors have found that the film-forming property (dispersibility) is good when the graphene dispersion is used for film formation.
[0015] Furthermore, the present inventors have found that when the graphene resin powder is used as a negative electrode material for a secondary battery, a battery having a high high-rate discharge capacity retention rate can be obtained.
[0016] Hereinafter, the present invention will be described in detail with reference to one embodiment.
[0017] In this specification, the description of "XX to YY" means "more than XX and less than YY". In addition, in this specification, for a numerical range (for example, a range of content, etc.), the lower limit and upper limit described in stages can be independently combined. In addition, in the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the examples.
[0018] In this specification, "graphene" refers to "a sheet-like substance containing sp2-bonded carbon atoms of 10 layers or less".
[0019] In this specification, "modified graphite" refers to "a flaky substance containing sp2-bonded carbon atoms with a size (long side) of 0.1 nm to 50 μm, more than 10 layers and less than 2000 layers (excluding graphene)". The size of the "modified graphite" is measured using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, model S-3400NX). The thickness of the "modified graphite" is calculated using an X-ray diffraction device (manufactured by PANalytical, model X'Pert PRO) and the number of layers is calculated based on the interlayer spacing of the (002) diffraction line and the thickness of the crystal.
[0020] In this specification, "graphene resin powder" means "powder in which graphene and modified graphite are coated with resin".
[0021] (Graphene dispersion)
[0022] The graphene dispersion of the present embodiment contains graphene, a polymer, and a solvent, and further contains modified graphite and other components as necessary.
[0023] It should be noted that, as described in the Examples, the dispersibility of the graphene dispersion is measured by absorbance using a spectrophotometer.
[0024] The viscosity of the graphene dispersion is not particularly limited as long as it is 500 to 10000 mPa·s when measured at a measurement temperature of 25° C. and a rotation speed of 50 rpm, and may be 700 to 8000 mPa·s.
[0025] When the viscosity of the graphene dispersion is 500 mPa·s or more when measured at a temperature of 25°C and a rotation speed of 50 rpm, structural viscosity is easily exhibited, and graphene becomes less likely to aggregate. On the other hand, when the viscosity of the graphene dispersion is 10,000 mPa·s or less when measured at a temperature of 25°C and a rotation speed of 50 rpm, workability such as coating properties can be improved.
[0026] The viscosity of the graphene dispersion is not particularly limited when measured at a measuring temperature of 25°C and a rotation speed of 5 rpm, and may be 600 to 50,000 mPa·s, or 840 to 40,000 mPa·s. When the viscosity of the graphene dispersion is 600 mPa·s or more when measured at a measuring temperature of 25°C and a rotation speed of 5 rpm, the surface tension of the solvent becomes greater, and a uniform coating film can be obtained. On the other hand, when the viscosity of the graphene dispersion is 50,000 mPa·s or less when measured at a measuring temperature of 25°C and a rotation speed of 5 rpm, the operability such as coating properties can be improved, and a continuous coating film without uncoated areas can be obtained.
[0027] The value obtained by dividing the viscosity of the graphene dispersion measured at a rotation speed of 5 rpm by the viscosity of the graphene dispersion measured at a rotation speed of 50 rpm (hereinafter, sometimes referred to as "viscosity ratio") is not particularly limited as long as it is 1.2 to 5.0, and can be 2.0 to 4.0. By making the above-mentioned viscosity ratio above the above-mentioned lower limit, the graphene dispersion exhibits structural viscosity. This is because the secondary bonds between polymers exert a repulsive force that is nearly 10 times that of the van der Waals force between graphene. Therefore, graphene is stably dispersed even at a high concentration, and the aggregation of graphene and modified graphite can be reduced. In addition, by making the above-mentioned viscosity ratio below the above-mentioned upper limit, the graphene dispersion has moderate fluidity. Therefore, it is suitable for coating during film formation and can form a continuous and homogeneous film.
[0028] It should be noted that as a method for adjusting the above-mentioned viscosity ratio to within the above-mentioned range (obtaining the optimal structural viscosity), for example, the polymer is a specified anionic polymer; a specified amount (relatively small amount) of a polymer with a large weight average molecular weight is used; a polymer with an etherification degree of 0.5 to 2.2 is used, etc.
[0029] In addition, the "etherification degree" in this specification refers to the value measured by the nitric acid methanol method.
[0030] <Graphene>
[0031] The graphene is not particularly limited as long as it is graphene in the graphene dispersion. For example, the graphene may be graphene obtained using modified graphite as a raw material.
[0032] There is no particular limitation on the method for producing graphene from modified graphite. For example, mechanical exfoliation, CVD, oxidation-reduction, chemical exfoliation, etc. may be mentioned. These methods may be used alone or in combination of two or more.
[0033] The content of carbon atoms in graphene is not particularly limited, and may be 95% by mass or more, 99% by mass or more, or 100% by mass.
[0034] The content of impurities in graphene is not particularly limited, and may be 5% by mass or less, 1% by mass or less, or 0% by mass.
[0035] The size of graphene is not particularly limited, and may be 0.1 nm to 50 μm, 0.5 nm to 10 μm, or 0.1 μm to 2 μm. It should be noted that the size of graphene refers to the longer side (long side) of the longitudinal and lateral directions of graphene.
[0036] When the size of graphene is 0.1 nm or more, the thermal conductivity of graphene is improved. On the other hand, when the size of graphene is 50 μm or less, the dispersibility of graphene is improved.
[0037] The content of graphene in the graphene dispersion is not particularly limited, and may be 0.1% to 25% by mass, 1.0% to 15% by mass, or 3.0% to 10% by mass relative to the solvent in the graphene dispersion.
[0038] <<Modified graphite>>
[0039] Modified graphite can be produced, for example, from natural graphite.
[0040] The modified graphite may contain no atoms other than carbon atoms, or may contain atoms other than carbon atoms, for example, it may contain 10% by mass or less of oxygen atoms. When the content of oxygen atoms is 10% by mass or less, the thermal conductivity of the obtained graphene is improved.
[0041] The content of carbon atoms in the modified graphite is not particularly limited, and may be 70% to 100% by mass, 80% to 98% by mass, or 85% to 95% by mass.
[0042] The size of the modified graphite is not particularly limited as long as it is 0.1 nm to 50 μm, and may be 0.5 nm to 20 μm. The size of the modified graphite is the longer side (long side) of the longitudinal and lateral directions of the modified graphite.
[0043] When the size of the modified graphite is 0.1 nm or more, the thermal conductivity of the modified graphite is improved. On the other hand, when the size of the modified graphite is 50 μm or less, the dispersibility of the modified graphite is improved.
[0044] The number of layers of modified graphite is not particularly limited as long as it is greater than 10 and less than 2000 layers. From the viewpoint of improving flexibility and dispersibility, it may be greater than 10 and less than 200 layers, or greater than 10 and less than 30 layers.
[0045] <Polymer>
[0046] As a polymer, its weight average molecular weight is 10,000 to 800,000, and it is dissolved or dispersed in a solvent. In addition, as long as it shows the property of causing high viscosity under low shear rate conditions and reduced viscosity under high shear rate conditions (property of structural viscosity) in the dispersion, there is no particular limitation. The polymer can be any water-soluble polymer or water-insoluble polymer, or it can be an anionic polymer. In addition, when the polymer has a strong affinity for graphene, it becomes easy to coat graphene. Therefore, graphene and modified graphite become less likely to agglomerate or precipitate, and can be stored for a long time.
[0047] It should be noted that, in this specification, the "weight average molecular weight of the polymer" can be measured by gel permeation chromatography [GPC apparatus (HLC-8120GPC) manufactured by Tosoh Corporation, column (TSK-GEL, α-M×2 roots) manufactured by Tosoh Corporation, flow rate: 1 mL / min] using polystyrene with a known molecular weight as a standard substance.
[0048] <<Water-based polymer>>
[0049] There are no particular restrictions on the aqueous polymer, and examples thereof include thickening polysaccharides with gelling ability such as xanthan gum, welan gum, succinoglycan, guar gum, locust bean gum, tamarind gum, pectin and their derivatives, carboxymethyl cellulose (CMC) salts, hydroxyethyl cellulose, alginates, glucomannan, agar, λ-carrageenan, etc.; synthetic resins such as polyvinyl alcohol with a weight average molecular weight of 100,000 to 150,000, polymers with a weight average molecular weight of 100,000 to 150,000 containing alkyl methacrylate as the main component, and cross-linked acrylic acid polymers; PEG-based nonionic thickeners (surfactants) with HLB 8 to 12, etc.
[0050] <<Anionic polymer>>
[0051] The functional group of the anionic polymer is not particularly limited, and examples thereof include a carbonyl group, a hydroxyl group, a sulfonic acid group, and a phosphoric acid group.
[0052] There are no particular restrictions on the anionic polymer, but from the viewpoint of hydrogen bonding between hydroxyl groups and easy to show structural viscosity, for example, it can be a natural or semi-synthetic polymer carboxylic acid, and examples include salts having a carboxyl group such as alginic acid, carboxymethyl cellulose, hydroxycarboxymethyl cellulose, carboxymethylated starch, gum arabic, gum tragacanth, pectin, and hyaluronic acid.
[0053] The content of the polymer in the graphene dispersion is not particularly limited, and can be 1 to 100 mg / g, or 5 to 50 mg / g relative to the solvent in the graphene dispersion. When the content of the polymer in the graphene dispersion is 1 mg / g or more, structural viscosity is exhibited, and graphene becomes less likely to agglomerate. On the other hand, when the content of the polymer in the graphene dispersion is 100 mg / g or less, the surface resistance during film formation is reduced and the coating property (operability) of the graphene dispersion is improved.
[0054] As for the weight average molecular weight of the polymer, there is no particular limitation as long as it is 10,000 to 800,000, and it can be 50,000 to 600,000, or 100,000 to 500,000. When the weight average molecular weight of the polymer is 10,000 or more, the viscosity ratio of the graphene dispersion can be adjusted to 1.2 or more, the graphene dispersion exhibits structural viscosity, and the graphene becomes less likely to agglomerate. On the other hand, when the weight average molecular weight of the polymer is 800,000 or less, the operability such as coating property is improved.
[0055] The degree of etherification of the polymer is not particularly limited, and may be 0.5 to 2.2, or 0.7 to 1.5. When the degree of etherification of the polymer is 0.5 to 2.2, structural viscosity is likely to be exhibited.
[0056] Usually, polymer is sometimes used as thickener to disperse nanofiller. At this time, relative to the solvent, the amount of polymer (thickener) is usually at least 200mg / g or more. The polymer (thickener) is adsorbed on solid substances such as fillers, and the concentration of the polymer (thickener) in the solvent decreases. Therefore, in order to obtain the structural viscosity required for dispersion, the nanofiller needs a large amount of polymer (thickener). However, when the amount of polymer (thickener) is large, when it becomes a film, the polymer (thickener) increases the surface resistance and thus deteriorates the conductivity.
[0057] In the graphene dispersion of this embodiment, since graphene is a dispersoid, the amount of polymer (thickener) adsorbed on the solid material is small due to its shape. Even if the polymer (thickener) is a small amount less than 200 mg / g, the dispersibility can be improved and the surface resistance can be reduced.
[0058] <Solvent>
[0059] The solvent is not particularly limited as long as it can disperse graphene or dissolve or disperse polymers, and may be a polar solvent.
[0060] There are no particular restrictions on polar solvents, for example, water, methanol, ethanol, 1-propanol, 2-propanol (isopropyl alcohol (IPA)), butanol, acetone, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, etc. can be cited. These can be used alone or in combination of two or more. Among them, in terms of high affinity with graphene, any one of water, methanol, ethanol, 1-propanol, 2-propanol, N-methylpyrrolidone, N,N-dimethylformamide and a mixed solvent of at least two of them can be selected. A mixed solvent containing water and alcohol can be selected, or water / 2-propanol with a mixing ratio (volume ratio) of 50 / 50 to 70 / 30 can be selected.
[0061] It should be noted that, when a non-polar solvent is used as the solvent, graphene is not easily dispersed in the solvent.
[0062] <Other ingredients>
[0063] The graphene dispersion of this embodiment may also contain other components. As other components, there are no particular restrictions, and may contain nanofillers; fillers such as expanded graphite and flaky graphite (except nanofillers); thickeners, viscosity regulators, resins, curing agents, flame retardants, foaming agents, ultraviolet absorbers and other additives.
[0064] In the solid component (i.e., components other than the solvent) of the graphene dispersion of this embodiment, the total amount of graphene, modified graphite and polymers with a weight average molecular weight of 10,000 to 800,000 can be 60% by mass or more, 80% by mass or more, 90% by mass or more, 95% by mass or more, or 100% by mass.
[0065] <Method for preparing graphene dispersion>
[0066] The method for producing the graphene dispersion liquid of the present embodiment is not particularly limited, and a known method for producing a graphene dispersion liquid can be used.
[0067] For example, the modified graphite is put into a solvent and liquid-phase exfoliated by ultrasonic dispersion, etc., and then a polymer is put into the solvent after exfoliation into a graphene state, and a mixing treatment is performed under vacuum using mechanical stirring, etc. to obtain a graphene dispersion. The amount of modified graphite added to the solvent can be 5 to 100 mg / g, or 10 to 70 mg / g. When the amount of modified graphite added to the solvent is too small, the concentration of graphene in the obtained graphene dispersion becomes low. On the other hand, when the amount of modified graphite added to the solvent is too large, the modified graphite is not easy to exfoliate and is not easy to become graphene.
[0068] <Graphene resin film>
[0069] A graphene resin film is formed using the graphene dispersion of this embodiment.
[0070] <<Method for producing graphene resin film from graphene dispersion>>
[0071] The graphene dispersion of the present embodiment has graphene almost uniformly present in the solvent, and modified graphite may also be almost uniformly present. As a result, the film formed using the graphene dispersion has good film-forming properties and becomes a film containing graphene almost uniformly. There is no particular limitation on the method for manufacturing a film formed using the graphene dispersion of the present embodiment, and for example, a method of coating the graphene dispersion on a desired surface of a substrate and curing it to form a film can be cited.
[0072] The material of the substrate for forming a film formed using the graphene dispersion of the present embodiment is not particularly limited as long as the desired film can be formed, and examples thereof include ceramics such as glass, silica, alumina, titanium oxide, silicon carbide, silicon nitride, and aluminum nitride; metals such as silicon, aluminum, iron, and nickel; and thermoplastic resins such as acrylic resins, polyesters, polycarbonates, polyamides, polyimides, polyphenylene sulfide, polyetheretherketone, polyphenylene ether, polyethernitrile, polyamideimide, polyethersulfone, polysulfone, and polyetherimide.
[0073] As for the film formed by the graphene dispersion liquid using the present embodiment, there is no particular limitation as long as a film formed by the graphene dispersion liquid can be formed, for example, film-like bodies such as films and sheets (including fabrics or non-woven fabrics formed by fibers); molded bodies other than film-like bodies; powders and granules, etc.
[0074] In order to improve the adhesion with the film formed using the graphene dispersion liquid of this embodiment, the surface of the substrate may be subjected to a corona discharge treatment or a plasma discharge treatment.
[0075] As a coating method for forming a film formed using the graphene dispersion of the present embodiment, various general coating methods can be used according to the viscosity of the graphene dispersion, the shape and size of the desired film. There are no particular restrictions on the coating method, for example, cast / immersion method, doctor blade coating method, knife coating method, rod coating method, spin coating method, gravure coating method, screen coating method, spraying method using a sprayer, etc. can be cited.
[0076] After the graphene dispersion is applied to the substrate, the object to be coated with the graphene dispersion may be subjected to a heat treatment in order to remove the dispersion medium in the graphene dispersion. The heat treatment temperature varies depending on the volatility of the solvent, the type of substrate, the heating environment, and the function to be imparted by the film forming properties. When the substrate is a ceramic or metal, the heat treatment temperature is 50 to 300°C, and when the substrate is a thermoplastic resin, the heat treatment temperature is 20 to 250°C. There are no particular restrictions as long as these temperatures do not deteriorate the graphene or the substrate.
[0077] The film formed using the graphene dispersion of this embodiment can be fixed on a substrate or peeled off from the substrate. The film fixed on the substrate can impart functions such as electrical conductivity, thermal conductivity, and electromagnetic wave absorption to the substrate.
[0078] The thickness of the film formed by the graphene dispersion of the present embodiment is not particularly limited, and may be 50 μm or less, or 30 μm or less. When the film thickness is 50 μm or less, it is not easy to cause a decrease in leveling properties. It should be noted that as long as it is within the range of obtaining a uniform film, there is no particular limitation on the lower limit of the film thickness.
[0079] <Molded products other than films formed using graphene dispersion>
[0080] The graphene dispersion of this embodiment can be used as a material for a molded product by mixing the graphene dispersion with other organic polymer materials, etc., in addition to a film. For example, it can be used as a material for a molded product having electrical conductivity, thermal conductivity, electromagnetic wave absorption, etc., especially a material for a molded product such as an electrode that requires electrical conductivity.
[0081] (Graphene resin powder)
[0082] The graphene resin powder of the present embodiment is obtained by drying the graphene dispersion of the present embodiment.
[0083] Even if the graphene resin powder obtained by drying the graphene dispersion is dispersed again in a solvent to form a film, the film can be formed without agglomeration between graphenes or between a mixture of graphene and modified graphite.
[0084] The method of drying the graphene dispersion to prepare the graphene resin powder is not particularly limited, and examples thereof include a method of preparing the graphene resin powder by volatilizing the solvent in the graphene dispersion by vacuum heating at 60 to 120°C.
[0085] There is no particular limitation on the method of dissolving or dispersing the graphene resin powder in the solvent again. For example, the graphene resin powder may be put into the solvent and stirred at a specified temperature (even room temperature) by mechanical stirring, ultrasound, high-pressure homogenizer, etc.
[0086] There is no particular restriction on the solvent for re-dissolving the graphene resin powder. For example, polar solvents such as water, methanol, ethanol, 1-propanol, 2-propanol, butanol, acetone, acetonitrile, tetrahydrofuran, dimethyl sulfoxide, dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, etc. can be cited. These can be used alone or in combination of two or more. Among them, in terms of high affinity with graphene, any one of water, methanol, ethanol, 1-propanol, 2-propanol, N-methylpyrrolidone, N,N-dimethylformamide and a mixed solvent of at least two of them can be selected.
[0087] The film forming method using the dispersion liquid in which the graphene resin powder is redissolved is not particularly limited, and a method similar to the film forming method using the graphene dispersion liquid can be used.
[0088] <Graphene dispersion for negative electrode>
[0089] The graphene resin powder of the present embodiment can be used as a graphene dispersion for a negative electrode by adding a negative electrode active material and a binder for a graphene dispersion for a negative electrode.
[0090] <<Negative electrode active material>>
[0091] There are no particular limitations on the negative electrode active material as long as it can be doped or embedded with lithium ions. Examples of the negative electrode active material include metal Li; alloys thereof such as tin alloys, silicon alloys, and lead alloys; and Li k Fe2O3 (in this paragraph, k represents 0<k≤4), Li k Fe3O4、Li k Metal oxide materials such as WO2; conductive polymer materials such as polyacetylene; amorphous carbon materials such as hard carbon; artificial graphite such as highly graphitized carbon materials; carbon powders such as natural graphite; carbon materials such as carbon black and carbon fiber. These negative electrode active materials can be used alone or in combination.
[0092] <<Binder for graphene dispersion for negative electrode>>
[0093] The binder for the graphene dispersion for the negative electrode is not particularly limited as long as it is used to bond the particles of the active material and the conductive carbon material, or to bond the conductive carbon material to the current collector. As the binder for the graphene dispersion for the negative electrode, for example, acrylic resins; polyurethane resins; cellulose resins such as carboxymethyl cellulose; synthetic rubbers such as styrene butadiene rubber and fluororubber; conductive resins such as polyacetylene; high molecular weight compounds containing fluorine atoms such as polyvinylidene fluoride, etc. In addition, the binder for the graphene dispersion for the negative electrode can also be a modified product, a mixture or a copolymer of these resins. These binders can be used alone or in combination. In addition, when used in an aqueous mixture ink, an aqueous medium binder can be used as a binder. As the form of the aqueous medium binder, water-soluble type, emulsion type, hydrosol type, etc. can be mentioned, which can be appropriately selected.
[0094] The graphene dispersion for the negative electrode may further contain a film-forming aid, a defoaming agent, a leveling agent, an antiseptic, a pH adjuster, a viscosity adjuster, and the like as necessary.
[0095] The graphene dispersion for negative electrode can be used for electrodes for lithium ion secondary batteries, electrodes for electric double layer capacitors, primer layers of electrodes for lithium ion capacitors, and the like.
[0096] <<Battery negative electrode mixture layer>>
[0097] The negative electrode mixture layer of the battery can be obtained by applying the graphene dispersion for the negative electrode onto the current collector and drying it.
[0098] -Current collector-
[0099] The material and shape of the current collector used for the electrode are not particularly limited, and the current collector used in various batteries can be appropriately selected. As the material of the current collector, for example, metals such as aluminum, copper, nickel, titanium, and stainless steel can be cited; alloys of at least two of them, etc. In addition, as a shape, a foil on a flat plate is usually used, but a current collector with a roughened surface, a foil-shaped current collector with holes, and a mesh-shaped current collector can also be used.
[0100] As a method for coating the electrode graphene dispersion on the current collector, there is no particular restriction, and a known method can be used. As the method, for example, a die coating method, a dip coating method, a roller coating method, a blade coating method, a scraping method, a spray coating method, a gravure coating method, a screen printing method, an electrostatic coating method, etc. can be cited. As a drying method, it is possible to use placement drying, air supply drying, warm air drying, infrared heating drying, far infrared heating drying, but it is not particularly limited thereto. In addition, the current collector can be calendered with a lithographic press or a calendering roller after coating.
[0101] (Battery)
[0102] The battery of the present embodiment is, for example, a lithium ion secondary battery or the like using a negative electrode as a negative electrode mixture layer of the battery, a positive electrode, an electrolyte solution, a separator, and the like.
[0103] Hereinafter, a lithium ion secondary battery will be described as an example.
[0104] <Electrolyte>
[0105] As the electrolyte, an electrolyte obtained by dissolving a lithium-containing electrolyte in a non-aqueous solvent can be used. As the non-aqueous solvent, there is no particular limitation, for example, carbonates such as ethylene carbonate and propylene carbonate; lactones such as γ-butyrolactone and γ-valerolactone; cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran; esters such as methyl formate and methyl acetate, etc. In addition, these solvents can be used alone or in combination of two or more. In addition, the above-mentioned electrolyte can also be retained in a polymer matrix to form a gel-like polymer electrolyte. As the polymer matrix, acrylate resins having polyalkylene oxide segments, polyphosphazene resins having polyalkylene oxide segments, polysiloxanes having polyalkylene oxide segments, etc. can be cited, but are not limited to these.
[0106] Examples of the electrolyte include LiBF4, LiPF6, LiAsF6, LiSbF6, and LiCF3SO3, but are not limited thereto.
[0107] <Spacer>
[0108] Examples of the spacer include polyethylene nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and spacers obtained by subjecting these materials to a hydrophilic treatment, but the spacer is not limited thereto.
[0109] Example
[0110] Next, the present invention will be specifically described by way of Examples, but the present invention is not limited to these Examples at all.
[0111] (Example 1)
[0112] [Method for preparing graphene dispersion]
[0113] 20.00 g of modified graphite-1 (manufactured by XG sciences, grade M, size (long side): 15 μm, number of layers: 20 layers) was put into 575.00 g of a mixed solvent (volume ratio: 60 / 40) of deionized water and 2-propanol as a solvent, and treated with an ultrasonic homogenizer (manufactured by SMT Co., Ltd., UH-600S) for 60 minutes to obtain graphene from the modified graphite. Thereafter, 28.80 g of carboxymethylated starch (manufactured by Nichiyo Chemical Co., Ltd., trade name: carboxymethyl starch, weight average molecular weight: 180,000, degree of etherification 0.90-1.10) as a polymer was added, and a planetary mixer was used to mix and treat under vacuum for 20 minutes to prepare a graphene dispersion. The prepared graphene dispersion was used as dispersion 1.
[0114] The following evaluations were performed using the obtained dispersion 1. The evaluation results are shown in Table 1-1.
[0115] [Evaluation method of graphene dispersion]
[0116] <Measurement of graphene concentration, modified graphite concentration, and polymer concentration>
[0117] 20.00g of modified graphite-1 (manufactured by XG sciences, grade M, size (long side): 15μm, number of layers: 20 layers) was put into 575.00g of a mixed solvent (volume ratio: 60 / 40) of deionized water and 2-propanol as a solvent, and 100.00g of the material obtained by treating it with an ultrasonic homogenizer (manufactured by SMT Co., Ltd., UH-600S) for 60 minutes was centrifuged with a centrifuge (manufactured by Hitachi Koki Co., Ltd., model: R-22N, 1000rpm, 10 minutes). The supernatant was 90.00g and the sedimented residue was 10.00g. After drying 90.00g of the supernatant at 100°C and evaporating the solvent, the solid content was 0.62g. Therefore, 90.00g of the supernatant contained 0.62g of graphene and 89.38g of solvent. The graphene concentration (mg / g) was calculated by dividing the graphene mass (0.62 g) by the solvent mass (89.38 g).
[0118] It should be noted that the graphene amount (g) in Table 1-1 and Table 1-2 is a value obtained by multiplying the calculated graphene concentration (mg / g) by the blending amount (g) of the solvent.
[0119] In Table 1-1 and Table 1-2, the modified graphite concentration (mg / g) and the polymer concentration (mg / g) are the values obtained by dividing the amount of modified graphite added (mg) by the amount of solvent added (g), and the values obtained by dividing the amount of carboxymethylated starch as a polymer (mg) by the amount of solvent added (g), respectively.
[0120] <Graphene size measurement>
[0121] The graphene size (long side) was confirmed to be 0.70 μm using an atomic force microscope (manufactured by Keysight Technologies, model: AFM / SPM7500). The AFM sample was prepared by spraying a graphene dispersion onto cleaved mica and drying it.
[0122] <Measurement of the number of graphene layers>
[0123] The thickness of graphene was measured using an atomic force microscope (AFM / SPM7500, manufactured by Keysight Technologies). As a result, it was confirmed that the number of graphene layers was less than 10, and modified graphite-1 had become graphene. The AFM sample was prepared by spraying a graphene dispersion on cleaved mica and drying it.
[0124] <Measurement of graphene dispersion viscosity>
[0125] The viscosity at 5 rpm and the viscosity at 50 rpm were measured at a measurement temperature of 25° C. using a B-type viscometer (manufactured by Horiba, Ltd., main body: LVT, cylindrical spindle: LV No. 4).
[0126] <Measurement of dispersibility of graphene dispersion>
[0127] <<Dispersion-1>>
[0128] The dispersion 1 was left to stand at room temperature (25° C.) for 1 month, and the precipitation and aggregation of graphene were visually confirmed and evaluated.
[0129] A: No precipitation or aggregation occurred.
[0130] B: A small amount of precipitation or agglomeration occurs.
[0131] C: A large amount of precipitation or agglomeration occurs.
[0132] <<Dispersion-2>>
[0133] Dispersion 1 was centrifuged (manufactured by Hitachi Koki Co., Ltd., model: CN-2060, rotor: RA-1508, 1000 rpm) for 10 minutes, 1 mL of the dispersion was collected from the upper layer, and diluted 100 times with a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) as a solvent to prepare a dilution. The absorbance (660 nm) of the prepared dilution was measured using a spectrophotometer (manufactured by JASCO Corporation, V-570), and the absorbance value was multiplied by 100 times.
[0134] [Evaluation of dispersibility and film-forming properties of graphene resin films]
[0135] Dispersion 1 was dropped onto a metal foil, applied with a bar coater, and dried at 85° C. for 10 minutes to remove the solvent, thereby forming a film with a thickness of 5 μm. The dispersibility and film-forming properties of the formed graphene resin film were visually evaluated.
[0136] <<Dispersibility>>
[0137] A: No agglutination.
[0138] B: Partial agglutination.
[0139] C: Overall agglutination.
[0140] <<Film-forming property>>
[0141] A: A uniform continuous film can be obtained.
[0142] B: There is a region where a uniform continuous film cannot be formed partially.
[0143] C: Unable to form a film.
[0144] <Evaluation of electrical conductivity>
[0145] The surface resistance of the graphene resin film with a thickness of 30 μm produced by the above method was measured using Loresta (manufactured by Mitsubishi Chemical Analytical Co., Ltd.). It should be noted that the surface resistance value can be 1.0 Ω / □ or less, and can be 1.0×10 -1 Ω / □ or less.
[0146] [Evaluation of dispersibility of graphene resin powder]
[0147] After the solvent of the dispersion 1 was heated to 100° C. and dried, the dried powder was pulverized in a mortar to prepare a graphene resin powder coated with a polymer.
[0148] Using a dispersing rotor (Three-One Motor manufactured by Shinto Science Co., Ltd.) with a force weaker than that of ultrasonic waves, the graphene resin powder was dissolved in 575 g of a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) at 500 rpm × 10 minutes each to prepare a graphene redispersion liquid. The graphene redispersion liquid was treated with a centrifuge (manufactured by Hitachi Koki Co., Ltd., model: CN-2060, rotor: RA-1508, 1000 rpm) for 10 minutes, 1 mL of the dispersion liquid was taken from the upper layer, and the dilution liquid was prepared by diluting it 100 times with a solvent. The absorbance (660 nm) of the prepared dilution liquid was measured and multiplied by 100 times as the absorbance value.
[0149] (Examples 2 to 8, Comparative Examples 1 to 5)
[0150] Graphene dispersions (dispersions 2 to 13) having the compositions described in Tables 1-1 and 1-2 were prepared in the same manner as in Example 1. Furthermore, the prepared graphene dispersions (dispersions 2 to 13) were used to perform the same evaluations as in Example 1. The evaluation results are shown in Tables 1-1 and 1-2.
[0151] It should be noted that, specifically, dispersion 9 without polymer was used as Comparative Example 1, dispersion 10 in which a predetermined amount of surfactant was added instead of the polymer was used as Comparative Example 2, dispersions 11 and 12 whose viscosity ratios did not conform to those of the embodiment were used as Comparative Examples 3 and 4, and dispersion 13 in which a nanofiller exhibiting conductivity similar to that of graphene was added instead of modified graphite was used as Comparative Example 5.
[0152] [Table 1-1]
[0153]
[0154] [Table 1-2]
[0155]
[0156] In addition, the compounding components described in Table 1-1 and Table 1-2 are as follows in detail.
[0157] Modified graphite-2 (manufactured by XG Sciences, grade M, size (long side): 25 μm, number of layers: 20 layers).
[0158] Nanofiller (alumina nanofiller, manufactured by Sumitomo Chemical Co., Ltd., product name: AA-03, size 0.4 μm).
[0159] Carboxymethylated starch (manufactured by Nichiyo Chemical Co., Ltd., product name: carboxymethyl starch, weight average molecular weight: 340,000, degree of etherification: 0.90 to 1.10).
[0160] Carboxymethyl cellulose (manufactured by Nippon Paper Industries, Ltd., product name: MAC350HC, weight average molecular weight: 340,000, degree of etherification: 0.78 to 0.88).
[0161] Hydroxyethyl cellulose (manufactured by Sumitomo Seika Chemicals, Ltd., product name: HEC-CF-H, weight average molecular weight: 700,000, degree of etherification: 0.90 to 1.20).
[0162] Polyvinyl alcohol-1 (manufactured by Mitsubishi Chemical Corporation, product name: EG-05C, weight average molecular weight: 120,000, degree of saponification: 87 mol%).
[0163] Polyvinyl alcohol-2 (manufactured by Kuraray Co., Ltd., product name: PVA-217, weight average molecular weight: 1700).
[0164] ·Polyacrylic acid (manufactured by Nippon Shokubai Co., Ltd., product name: DL-100, weight average molecular weight: 3500).
[0165] Surfactant (manufactured by Kao Corporation, product name: NEOPELEX G-65, molecular weight: 350).
[0166] In this way, by dispersing graphene and a polymer with a weight average molecular weight of 10,000 to 800,000 in a solvent, the viscosity measured using a B-type viscometer at a measuring temperature of 25°C and a rotation speed of 50 rpm is adjusted to 500 to 10,000 (mPa·s), and the value obtained by dividing the viscosity measured using a B-type viscometer at a measuring temperature of 25°C and a rotation speed of 5 rpm by the viscosity measured using a B-type viscometer at a measuring temperature of 25°C and a rotation speed of 50 rpm (viscosity ratio) is adjusted to 1.2 to 5.0 (becoming thixotropic (becoming a dispersion with structural viscosity)), thereby obtaining a graphene dispersion having excellent dispersibility and capable of forming a graphene resin film with high conductivity. This can be seen by comparing Examples 1 to 8 with Comparative Examples 1 to 5.
[0167] <Preparation of graphene dispersion for negative electrode>
[0168] 10.00 g of graphene resin powder prepared from dispersion 1, 85.00 g of spherical graphite as a negative electrode active material, 5.00 g of a negative electrode binder, and 122.00 g of a mixed solvent of deionized water and 2-propanol (volume ratio: 60 / 40) were added to a planetary mixer, kneaded under vacuum, and further mixed with a 48% aqueous dispersion of styrene butadiene emulsion as a binder for a graphene dispersion for a negative electrode, thereby obtaining a graphene dispersion for a negative electrode having a solid content concentration of 45%. Dispersions 2 to 13 were also prepared in the same manner.
[0169] <Production of battery negative electrode mixture layer>
[0170] A battery electrode mixture layer is made using a graphene dispersion for the negative electrode and a copper foil (thickness 18 μm) as a current collector. Use a scraper to apply the graphene dispersion for the negative electrode to a specified thickness. Dry it in a vacuum at 120°C for 1 hour and punch it into 18 mmΦ. Furthermore, clamp the punched battery negative electrode mixture layer with a super steel pressing plate to apply a pressure of 1000 to 3000 kg / cm 2 The weight per unit area is 7-9 mg / cm 2 , thickness of 40-60 μm and electrode density of 1.6 g / cm 3 Thereafter, the resulting product was dried in a vacuum dryer at 120° C. for 12 hours to prepare a negative electrode for evaluation.
[0171] <Manufacturing of positive electrode>
[0172] Add 90.00 g of lithium nickelate as a positive electrode active material, 5.00 g of acetylene black (HS-100 manufactured by Denka Co., Ltd.) as a conductive aid, 5.00 g of KF polymer W7300 (PVDF) as a positive electrode binder, and NMP into a planetary mixer and mix them to prepare a positive electrode mixture slurry with a solid content concentration of 67%. Use a scraper to apply the positive electrode mixture slurry to an aluminum foil (thickness 10 μm) with a specified thickness. Dry it in a vacuum at 120°C for 1 hour and punch it into 18 mmΦ. Furthermore, clamp the punched electrode with a super steel pressing plate, and apply a pressure of 1000 to 3000 kg / cm 2 After that, it was dried in a vacuum dryer at 120°C for 12 hours to prepare a positive electrode for evaluation. The thickness was about 80 μm and the electrode density was about 3.5 g / cm 3 .
[0173] <High rate discharge capacity retention rate>
[0174] Using the lithium ion battery test cell produced as described above, a constant current and constant voltage charge and discharge test was performed.
[0175] The charge is from a static potential at 3.6 mA / cm 2 The battery was charged at a constant current of 4.3 V. Then, the battery was switched to a constant voltage of 4.3 V and stopped when the current value dropped to 15.0 μA. The discharge was performed at each current density (3.6 mA / cm 2 (equivalent to 0.1C) and 72.0mA / cm 2 The constant current discharge was performed under the conditions of (equivalent to 2.0C) and the voltage was cut off at 2.8V. The ratio of the discharge capacity at 2.0C to the discharge capacity at 0.1C was evaluated as the high rate discharge capacity retention rate. The evaluation was performed according to the following criteria. The results of the evaluation according to the following criteria are shown in Tables 1-1 and 1-2.
[0176] A (excellent): The high-rate discharge capacity retention rate is 95% or more, which is acceptable.
[0177] B (good): The high-rate discharge capacity retention rate is 90% or more and less than 95%, which is acceptable.
[0178] C (slightly poor): The high-rate discharge capacity retention rate is 80% or more and less than 90%, which is acceptable.
[0179] D (bad): The high-rate discharge capacity retention ratio is less than 80%, which is unacceptable.
[0180] <Adhesive>
[0181] Styrene butadiene emulsion (SBR) (manufactured by JSR Corporation, product name: TRD2001, 48% solid content aqueous dispersion) as a binder for the graphene dispersion for the negative electrode.
[0182] Polyvinylidene fluoride (PVDF) as a positive electrode binder (manufactured by Kureha Corporation, product name: KF polymer W7300, weight average molecular weight of about 1,000,000).
[0183] <Electrode active material>
[0184] Positive electrode active material: lithium nickel oxide (manufactured by JFE Minerals Co., Ltd., product name: 503LP, average particle size: 11 μm).
[0185] Negative electrode active material: spherical graphite (Nippon Graphite Industries, Ltd., product name: CGB-20, average particle size 20 μm).
[0186] As can be seen from Table 1-1 and Table 1-2, the high rate discharge capacity retention of the batteries of Examples 1 to 8 shows better results than that of the batteries of Comparative Examples 1 to 5. In particular, since the dispersibility (absorbance) of the graphene resin powder is high and the film forming property of the graphene resin film is good, an electrode layer of a secondary battery with excellent high rate discharge capacity retention can be obtained.
Claims
1. A graphene dispersion, wherein: It is a graphene dispersion in which graphene and polymer are dispersed or dissolved in a solvent. The weight average molecular weight of the polymer is 10,000 to 800,000. The graphene dispersion has a viscosity of 500 to 10000 mPa·s when measured using a B-type viscometer at a temperature of 25° C. and a rotation speed of 50 rpm. The viscosity of the graphene dispersion measured by a B-type viscometer at a measuring temperature of 25° C. and a rotation speed of 5 rpm, divided by the viscosity of the graphene dispersion measured by a B-type viscometer at a measuring temperature of 25° C. and a rotation speed of 50 rpm, is 1.2 to 5.
0. The polymer is an anionic polymer or a water-based polymer, The anionic polymer is carboxymethylated starch, carboxymethyl cellulose or hydroxyethyl cellulose, The water-based polymer is polyvinyl alcohol with a saponification degree of 87 mol%, The solvent is a mixed solvent containing water and alcohol, The content of the polymer is 5 to 50 mg / g relative to the solvent. The etherification degree of the polymer is 0.5 to 2.2, The size of the graphene is 0.1 μm to 2 μm.
2. A graphene resin powder, wherein: The graphene dispersion according to claim 1 is dried.
3. A battery, wherein: The graphene resin powder according to claim 2 is used.
Citation Information
Patent Citations
Mixed liquid, resin composite material, and method for producing resin composite material
JP2012224810A
Graphene-dispersed liquid and preparation method thereof
JP2014009104A
Method for preparing three-dimensional porous nano composite material of graphene oxide-water soluble polymer
CN103881278A
Method for preparing multi-layer graphene
CN105084346A
Graphene-filled thermoset high-polymer compound and preparation method thereof
CN105924900A
